Pengembangan Sumber Daya PNS (Studi Kebijakan Pengembangan Sumber Daya PNS di Pemerintah Daerah Kabupaten Karimun) - * Helmi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2012)
Several country in the world showed to us that the success of a Country not only was determined by the nature wealth that was owned by him, but also was caused by the quality ofÂ human resources, this could be seen by us like the Singaporean country although his nature wealth did not overflow, but the development of this country could be made the example by us how to their manage human resources could be expect and in the long run made this country one of the countries that like that went up in this Asian part. Based on from various results of the research of the experts, the quality of human resources could bring an organization was successful and the success was determined by his competence. Human resource competence or soft skill was the characteristics of the attitude and the effective behavior in the development of this organization. Competency will push someone to have the best achievement so as to be able to be successful in the organization. The development of human resources was something important in an organization especially the organization of the Government, the availability of human resources did not only include the available quantity but also must be accompanied by the quality of the human resources personally. To create the quality of human resources especially the quality of PNS human resources in the Karimun Regional Government then presumably necessary him created a model development of PNS human resources that were based on competence that only was not valid in the level of the certain position but also the model of human resources of development competence must be able to in applied in all the PNS levels available that is from unsure that was lowest to unsure the tallest official. Results of the research showed that the Karimun Regional Government did not yet place a model competency especially for the staff and that had the standard of special competence was them who occupied the certain position that is in the level eselonering that was based on the provisions of regulations Number : 43 in 200I place directly Standard position of structural Competence.Keyword : Aparature, development